Lack of FSH2 alters phospholipid metabolism in Saccharomyces cerevisiae - Gowsalya, Ramachandran; Nachiappan, Vasanthi (International Journal of Scientific Research in Biological Sciences, 2018)
Alpha/beta hydrolase domain containing protein act as a key regulator of lipid metabolism is extensively studied in Saccharomyces cerevisiae. However, the function of FSH2 in lipid metabolism is still elusive, and we tried to understand the biological importance of FSH2 in Saccharomyces cerevisiae. In our study, a protein containing alpha/beta hydrolase domain and belonging to the family of serine hydrolase (FSH) also possessed motifs of lipase (GXSXG) and acyl transferase (HX4D) that were identified using in silico analysis. The overexpression of FSH2 in WT and fsh2Δ cells reduced the level of phospholipids, but in fsh2 strain increase in the cellular phospholipids, and this could be attributed to the formation of clumped aggregates and plasma membrane alteration were depicted using lipophilic fluorescent dye DiOC6. The current study suggested that the deletion of FSH2 altered the phospholipid homeostasis and membrane morphology .Together, our results shown that the FSH2 has a role in the phospholipid metabolism in Saccharomyces cerevisiae.